Growth and Isolation of Large Area Boron‐Doped Nanocrystalline Diamond Sheets: A Route toward Diamond‐on‐Graphene Heterojunction. (22nd November 2018) - Bogdanowicz, R.; Ficek, M.; Sobaszek, M.; Nosek, A.; Gołuński, Ł.; Karczewski, J.; Jaramillo‐Botero, A.; Goddard, W. A.; Bockrath, M.; Ossowski, T.
Abstract: Many material device applications would benefit from thin diamond coatings, but current growth techniques, such as chemical vapor deposition (CVD) or atomic layer deposition require high substrate and gas‐phase temperatures that would destroy the device being coated. The development of freestanding, thin boron‐doped diamond nanosheets grown on tantalum foil substrates via microwave plasma‐assisted CVD is reported. These diamond sheets (measuring up to 4 × 5 mm in planar area, and 300–600 nm in thickness) are removed from the substrate using mechanical exfoliation and then transferred to other substrates, including Si/SiO2 and graphene. The electronic properties of the resulting diamond nanosheets and their dependence on the free‐standing growth, the mechanical exfoliation and transfer processes, and ultimately on their composition are characterized. To validate this, a prototypical diamond nanosheet–graphene field effect transistor‐like (DNGfet) device is developed and its electronic transport properties are studied as a function of temperature. The resulting DNGfet device exhibits thermally activated transport (thermionic conductance) above 50 K. Below 50 K a transition to variable range hopping is observed. These findings demonstrate the first step towards a low‐temperature diamond‐based transistor. Abstract : Thin and boron‐doped diamond nanosheets are grown on tantalum foil substrates via microwave plasma‐assisted chemical vapor deposition. Free standing diamond nanosheets are transfered onto graphene resulting in a prototypical diamond nanosheet‐graphene field effect transistor‐like device. These findings demonstrate the first step towards a low‐temperature diamond‐based transistor.